THE EFFECT OF ASSERTIVE COMMUNICATION STYLE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING FACTOR - M. Saifur Rahman; Sulistyani Sulistyani; Tri Widayati (Universitas 17 Agustus 1945 Semarang, 2023)
The study of the influence of assertive communication style and organizational culture on employee performance with job satisfaction as an intervening factor was conducted by taking a sample of 72 respondents from the Al Ummah Education and Human Resources Foundation who were placed in Assalaam Integrated Islamic Junior High School Pekalongan City. From the results of the study, it was found that assertive communication style has a positive effect on job satisfaction; organizational culture has a positive impact on job satisfaction; Assertive communication style has a positive effect on employee performance, organizational culture has a positive impact on employee performance, job satisfaction has a positive effect on employee performance, job satisfaction does not mediate the influence of assertive communication style on employee performance, job satisfaction mediates the impact of organizational culture on employee performance.